Development of a continuous cell line from larval Atlantic cod ( Gadus morhua ) and its use in the study of the microsporidian, Loma morhua - Michael J. MacLeod; Nguyen T. K. Vo; Michael S. Mikhaeil; S. Richelle Monaghan; J. Andrew N. Alexander; Mandeep K. Saran; Lucy E. J. Lee (Journal of Fish Diseases, 2018)
In vitro cell culture methods are crucial for the isolation, purification and mass propagation of intracellular pathogens of aquatic organisms. Cell culture infection models can yield insights into infection mechanisms, aid in developing methods for disease mitigation and prevention, and inform commercial‐scale cultivation approaches. This study details the establishment of a larval cell line ( GML ‐5) from the Atlantic cod ( Gadus morhua ) and its use in the study of microsporidia. GML ‐5 has survived over 100 passages in 8 years of culture. The line remains active and viable between 8 and 21°C in Leibovitz‐15 (L‐15) media with 10% foetal bovine serum and exhibits a myofibroblast phenotype as indicated by immuno‐positive results for vimentin, α‐smooth muscle actin, collagen I and S‐100 proteins, while being desmin‐negative. GML ‐5 supports the infection and development of two microsporidian parasites, an opportunistic generalist ( Anncaliia algerae ) and cod‐specific Loma morhua . Using GML ‐5, spore germination and proliferation of L. morhua was found to require exposure to basic pH and cool incubation temperatures (8°C), in contrast to A. algerae , which required no cultural modifications. Loma morhua ‐associated xenoma‐like structures were observed 2 weeks postexposure. This in vitro infection model may serve as a valuable tool for cod parasitology and aquaculture research.